A fine-scale genetic analysis of hybrid incompatibilities in Drosophila. - Presgraves, D.C. (Genetics, 2003)
The sterility and inviability of species hybrids is thought to evolve by the accumulation of genes that cause generally recessive, incompatible epistatic interactions between species. Most analyses of the loci involved in such hybrid incompatibilities have suffered from low genetic resolution. Here I present a fine-resolution genetic screen that allows systematic counting, mapping, and characterizing of a large number of hybrid incompatibility loci in a model genetic system. Using small autosomal deletions from D. melanogaster and a hybrid rescue mutation from D. simulans, I measured the viability of hybrid males that are simultaneously hemizygous for a small region of the D. simulans autosomal genome and hemizygous for the D. melanogaster X chromosome. These hybrid males are exposed to the full effects of any recessive-recessive epistatic incompatibilities present in these regions. A screen of approximately 70% of the D. simulans autosomal genome reveals 20 hybrid-lethal and 20 hybrid-semilethal regions that are incompatible with the D. melanogaster X. In further crosses, I confirm the epistatic nature of hybrid lethality by showing that all of the incompatibilities are rescued when the D. melanogaster X is replaced with a D. simulans X. Combined with information from previous studies, these results show that the number of recessive incompatibilities is approximately eightfold larger than the number of dominant ones. Finally, I estimate that a total of approximately 191 hybrid-lethal incompatibilities separate D. melanogaster and D. simulans, indicating extensive functional divergence between these species' genomes.